One Month of Classic Therapeutic Ketogenic Diet Decreases Short Chain Fatty Acids Production in Epileptic Patients - Ferraris, Cinzia; Meroni, Erika; Casiraghi, Maria Cristina; Tagliabue, Anna; De Giorgis, Valentina; Erba, Daniela (Frontiers in Nutrition, 2021)
Ketogenic diet (KD), a high fat and very low carbohydrates diet, is used worldwide for the treatment of drug resistant epilepsy but, due to its composition, it might exert an impact on gut health. Even though data of KD effects on intestinal microbiota changes are recently emerging, its influence on the gut environment has been scarcely addressed so far. The aim of this study was to investigate whether 1 month of KD affects the gut environment in epileptic patients, by analyzing short chain fatty acids (SCFA) production and fecal water toxicity. A total of seven patients were enrolled. Stool samples were collected before (T0) and after 1 month of KD (4:1 ketogenic ratio) (T1). SCFA were determined by GC-FID and fecal water toxicity in Caco-2 cell culture by comet assay. Concentrations of SCFA significantly decreased after KD (p < 0.05): in particular, we found a 55% reduction of total SCFA level, a 64% reduction of acetate, 33% of propionate, and 20% of butyrate (p < 0.05). Cytotoxicity of fecal water extracted from stool samples was not significantly altered by diet, while genotoxicity was slightly decreased after KD (p < 0.05). Genotoxicity values were consistent with data previously obtained from a healthy Italian population. The present study suggests that 1 month of KD significantly reduce SCFA production. Since SCFA produced by gut microbiota exert many health promoting effects on either the gut environment or human metabolism, these results open a new branch of investigation into KD effects.